Efficient Recreation of t(11;22) EWSR1-FLI1+ in Human Stem Cells Using CRISPR/Cas9 - Raul Torres-Ruiz; Marta Martinez-Lage; Maria C. Martin; Aida Garcia; Clara Bueno; Julio Castaño; Juan C. Ramirez; Pablo Menendez; Juan C. Cigudosa; Sandra Rodriguez-Perales (Stem Cell Reports, 2017)
Efficient methodologies for recreating cancer-associated chromosome translocations are in high demand as tools for investigating how such events initiate cancer. The CRISPR/Cas9 system has been used to reconstruct the genetics of these complex rearrangements at native loci while maintaining the architecture and regulatory elements. However, the CRISPR system remains inefficient in human stem cells. Here, we compared three strategies aimed at enhancing the efficiency of the CRISPR-mediated t(11;22) translocation in human stem cells, including mesenchymal and induced pluripotent stem cells: (1) using end-joining DNA processing factors involved in repair mechanisms, or (2) ssODNs to guide the ligation of the double-strand break ends generated by CRISPR/Cas9; and (3) all-in-one plasmid or ribonucleoprotein complex-based approaches. We report that the generation of targeted t(11;22) is significantly increased by using a combination of ribonucleoprotein complexes and ssODNs. The CRISPR/Cas9-mediated generation of targeted t(11;22) in human stem cells opens up new avenues in modeling Ewing sarcoma.